2020
DOI: 10.1016/j.anbehav.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Spatially clustered resources increase male aggregation and mating duration in Drosophila melanogaster

Abstract: In environments where females mate multiply, males should adjust their behaviour and physiology in response to the prevailing perceived level of sperm competition. This expectation is well supported by both laboratory and field studies, but we don't yet know what mechanisms facilitate these plastic responses in natural populations. One way in which males appear to assess sperm competition risk is through encounter rates with conspecific males. Such encounter rates may be driven by the spatial distribution of r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…By confining flies to cages (albeit cages located in the shade), we also limit their ability to move to suitable microclimates, or to actively forage for mates or oviposition sites, all of which are behaviours that are highly sophisticated in Drosophila (e.g. Churchill et al . 2020; Malek & Long 2020; Churchill et al .…”
Section: Discussionmentioning
confidence: 99%
“…By confining flies to cages (albeit cages located in the shade), we also limit their ability to move to suitable microclimates, or to actively forage for mates or oviposition sites, all of which are behaviours that are highly sophisticated in Drosophila (e.g. Churchill et al . 2020; Malek & Long 2020; Churchill et al .…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely therefore that they may also be sensitive to intrasexual encounter rate among adults as a proxy for likely future larval competition. However despite the strong evidence for density and encounter rate effects on male behavior ( Bretman et al 2009 ; Fedorka et al 2011 ; Price et al 2012 ; Garbaczewska et al 2013 ; Moatt et al 2014 ; Hopkins et al 2019 ; Churchill et al 2020 ), and evidence that females are sensitive to the presence of conspecifics when making oviposition decisions ( Malek and Long 2020 ; Tait et al 2020 ), studies of the effect of female encounter rate on subsequent reproductive behavior are rare ( Gillmeister 1999 ). Recently, however, Fowler et al (2021) demonstrated that both male and female social environment can influence plasticity in various aspects of mating behavior, with interactions between the social environments of the mating pair playing an important role.…”
Section: Introductionmentioning
confidence: 99%
“…Ai et al (2017) used Raspberry Pi's to film RFID-tagged honeybees from the initial moult for a number of weeks to document the development of the waggle dance Churchill et al (2020). used Raspberry Pi cameras to film the spacing between foraging fruit flies throughout the day.…”
mentioning
confidence: 99%